Patient safety oriented to improve patient retention in oral health services - Tri Erri Astoeti (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Oral health service systems should be designed to promote patient health, protection, and must be in compliance with Indonesian laws that help protect patients from misuse of personal information. Patient safety is a new healthcare discipline that emphasizes the reporting, analysis, and prevention of medical or dental error that often lead to adverse healthcare events. Purpose: To describe correlation that patient safety would improve patent retention in oral health. Patient safety is an essential component of quality oral health care and dentist is encouraged to consider thoughtfully the environment in which they deliver dental care, while at the same time services and to implement practices that decrease a patient’s risk of injury or harm during the delivery of care. Reviews: Designing oral health care systems that focus on preventing errors is critical to assure patient safety. Some possible sources of error in oral health services are miscommunication, failure to review the patient’s medical history, and lack of standardized records, abbreviations, and processes. Conclusion: Patient safety would support patient satisfaction; therefore oral health services can increase patient retention.